2014
DOI: 10.2478/acve-2014-0027
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of DNA Damage Induced by Adrenaline in Human Lymphocytes in Vitro/Ispitivanja Oštećenja DNK Izazvanih Adrenalinom U Limfocitima Čoveka in Vitro

Abstract: Adrenaline is a neurotransmitter and hormone that plays an important role in physiological regulatory mechanisms. The objective of this study was to assess primary DNA damage in isolated human lymphocytes exposed to adrenaline using the in vitro comet assay. Dose-response of human lymphocytes was determined at concentration range of adrenaline from 0.01 μM to 300 μM for various treatment times (1h, 2h, 4h and 24h). The obtained results showed that adrenaline induced DNA damage at concentration range from 5 μM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…Beside GCs, other hormones involved in the stress response could explain variations in oxidative stress levels resulting from acute restraint-stress. For instance, adrenaline increases very rapidly during the first seconds to minutes after stress exposure, and has been shown to affect oxidative balance in vitro 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Beside GCs, other hormones involved in the stress response could explain variations in oxidative stress levels resulting from acute restraint-stress. For instance, adrenaline increases very rapidly during the first seconds to minutes after stress exposure, and has been shown to affect oxidative balance in vitro 58 .…”
Section: Discussionmentioning
confidence: 99%
“…conditions, catecholamines, particularly, adrenaline is released from sympathetic nervous system and adrenal medulla to serve a pivotal role in preparing the organism to fight or flight by modulating numerous physiological functions (2,3). However, excessive release of adrenaline, due to its pro-oxidant and auto-oxidation properties, generates enormous ROS that may induce detrimental effects on cells and tissues.…”
mentioning
confidence: 99%
“…These include loss of DNA integrity (4), cardiotoxicity (5), hepatotoxicity (6), cancer (7,8) and age-related disorders (9). It was reported that exogenous administration of adrenaline promoted a redox cycle and enhanced intra-cellular production of ROS (10). Notably, an already elevated release of adrenaline under acute stress could be further increased by chronic stressful conditions (11).…”
mentioning
confidence: 99%
“…On the other hand, increased CAT activity found in rats treated with adrenaline implies that CAT has an important protective role in removing free radicals produced in cells. This assumption is supported by studies of Djelić et al [10] and Radakovic et al [12] where catalase in cotreatment with adrenaline reduced DNA damage mediated by free radicals in human lymphocytes. Our results are in accordance with the study of Pereira et al [40] who reported that adrenaline plays a role in the oxidative stress in the lymphoid organs since adrenodemedullation affected the activities of antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 55%
“…One of the final products of oxidative metabolism-adrenochrome is able to stimulate oxidation of adrenaline in which superoxide anion (O 2 ·− ) and hydrogen peroxide (H 2 O 2 ) are formed. Besides, it was reported that catalase and quercetin diminished the DNA-damaging effect of adrenaline in vitro [12].…”
Section: Introductionmentioning
confidence: 99%